Anti-TGEV Miller Strain Infection Effect of Lactobacillus plantarum Supernatant Based on the JAK-STAT1 Signaling Pathway - Wang, Kai; Ran, Ling; Yan, Tao; Niu, Zheng; Kan, Zifei; Zhang, Yiling; Yang, Yang; Xie, Luyi; Huang, Shilei; Yu, Qiuhan; Wu, Di; Song, Zhenhui (Frontiers in Microbiology, 2019)
Transmissible gastroenteritis (TGE), caused by transmissible gastroenteritis virus (TGEV), is one many gastrointestinal inflections in piglets, characterized by diarrhea, and high mortality. Probiotics are ubiquitous bacteria in animal intestines, which have many functions, such as promoting intestinal peristalsis and maintaining the intestinal balance. We found that the supernatant of the Lp-1 strain of Lactobacillus plantarum, isolated in our laboratory, and named Lp-1s had marked anti-TGEV effect on IPEC-J2 cells. Lp-1s could induce large amounts of interferon-β in IPEC-J2 cells in the early stage (6 h) of infection with TGEV, and increased the level of phosphorylated signal transducer and activator of transcription and its nuclear translocation in the late stage (24–48 h) of infection. This resulted in upregulated expression of interferon-stimulated genes, and increased the transcription and protein expression of antiviral proteins, resulting in an anti-TGEV effect.